Family versus Nonfamily CEOs in Family Firms: A Multidisciplinary Review of Strategic Choices and Organizational Outcomes - Farah Qalbia; Seger Santoso (STIE KASIH BANGSA, 2025)
This qualitative literature review explores the strategic choices and organizational outcomes associated with family and nonfamily CEOs in family firms. Drawing from multidisciplinary studies, it highlights the contrasting leadership approaches of family CEOs, who emphasize long-term stability and socioemotional wealth (SEW), and nonfamily CEOs, who prioritize professionalization, transformative innovation, and market responsiveness. The analysis reveals that family firms benefit from the complementary strengths of both leadership types, with family CEOs fostering cohesion and legacy, and nonfamily CEOs driving performance and external orientation. Contextual factors such as firm lifecycle, industry dynamics, and governance structures are critical in determining the effectiveness of leadership models. The study underscores the need for adaptive leadership strategies in balancing cultural continuity and professional advancement, offering a nuanced understanding of family firm dynamics.